Anti-Inflammatory and Anti-asthmatic Effects of TMDCT Decoction in Eosinophilic Asthma Through Treg/Th17 Balance - Zhou, Yumei; Zhao, Haihong; Wang, Tieshan; Zhao, Xiaoshan; Wang, Ji; Wang, Qi (Frontiers in Pharmacology, 2022)
Tuo-Min-Ding-Chuan decoction (TMDCT) is a Traditional Chinese Medicine (TCM) formula consisting of twelve herbs that can relieve the symptoms and treat allergic asthma. Yet, the underlying mechanism of action is still unclear. In this study, we investigated the effect of TMDCT in regulating Treg/Th17 cells immune balance and explored potential metabolic and gut biomarkers associated with Treg and Th17 cells in eosinophilic asthma mice treated with TMDCT. We found that TMDCT increases Treg cells percentage and decreases Th17 cells percentage in the ovalbumin (OVA) -induced eosinophilic asthma mice model. Furthermore, L-Arabinono-1,4-lactone, Myo-inositol, Dl-lactate, Uracil, and 1-stearoyl-2- docosahexaenoyl-sn-glycero-3-phosphocholine, Phenaceturic acid, Ethylenediaminetetraacetic acid were identified as biomarkers as plasma metabolites, while genus Desulfovibrio, genus Butyricimonas, genus Peptoniphilus, genus Butyricimonas, genus mouse gut metagenome, and genus Peptostreptococcus as gut microbiota biomarkers. These results provide an experimental foundation for the treatment of allergic asthma with Chinese herbal compounds.